Influence of Situational Variables, Team Formation, and Playing Position on Match Running Performance and Social Network Analysis in Brazilian Professional Soccer Players - Aquino, Rodrigo; Carling, Christopher; Vieira, Luiz H. [UNESP]; Martins, Guilherme; Jabor, Gustavo; Machado, Joao; Santiago, Paulo; Garganta, Julio; Puggina, Enrico (Lippincott Williams & Wilkins, 2020)
Aquino, R, Carling, C, Palucci Vieira, LH, Martins, G, Jabor, G, Machado, J, Santiago, P, Garganta, J, and Puggina, E. Influence of situational variables, team formation, and playing position on match running performance and social network analysis of brazilian professional soccer players. J Strength Cond Res 34(3): 808-817, 2020-The purpose of this study was to investigate the independent and interactive effects of situational variables, opposition team formation, and playing position on running performance and network analysis in Brazilian professional soccer players (n = 22). Global positioning system technology was used to determine total distance covered, mean speed, maximum running speed, and distance covered in 6 speed ranges. Social network analysis was used to assess interpersonal coordination (team interactions characterized as successful passes [n = 3,033] between teammates). Observations of match running performance (n = 129) and network analysis (n = 108) were obtained. The main results were: (a) no interactive effects between team formation and playing position were observed for running and network variables (unclear to possibly); (b) matches played at home or against weaker opponents presented greater running demands and individual/global metrics of network analysis (likely to almost certain); (c) match outcome demonstrated influence only for running performance; matches in which the reference team won resulted in higher values than in matches lost; (d) when the reference team competed in 1-4-4-2 formation, this resulted in greater running demands than 1-4-2-3-1 formation (likely to almost certain); (e) reduced values of running performance variables were reported in central defenders compared with other positions. Central/external midfielders reported greater closeness/betweenness centrality, outdegree, and eigenvector compared with central/external defenders and forwards (likely to almost certain). The results from this study provide practical information to potentially impact on physical, tactical, and technical training.
Keywords: association football; time-motion analysis; interpersonal coordination; sports sciences